ABOUT THE OLDEST STONE-WORKING WORKSHOP OF KARAKUDUK-USTYURT PALEOLITH (Intent Research Scientific Journal, 2023)
The article uses modern technical and typological materials from the Karakuduk site in Ustyurt and the “deflation level” method used by archaeologist Derevianko and his colleagues to study the industry of the Argalant-1 site in Mongolia. As a result, the artifacts of the monument, first of all, were divided into three complexes according to the degree of preservation, and then, their technical and typological study was carried out and cultural and chronological divisions were identified. The first complex is attributed to the early Paleolithic. Artifacts of this complex suffered a strong deflation of surfaces. The complex, which we attributed to the Middle Paleolithic, has a desert tan of artifact surfaces and is culturally included in the bifacial facies. The materials of the third complex have only an external patina and look more recent, and we attributed them to the Late Paleolithic.